On the Ideal Convergence of Double Sequences in Locally Solid Riesz Spaces - A. Alotaibi; B. Hazarika; S. A. Mohiuddine (Abstract and Applied Analysis)
The aim of this paper is to define the notions of ideal convergence, I-bounded for double sequences in setting of locally solid Riesz spaces and study some results related to these notions. We also define the notion of I*-convergence for double sequences in locally solid Riesz spaces and establish its relationship with ideal convergence.